2023
DOI: 10.3389/fphar.2023.1133809
|View full text |Cite
|
Sign up to set email alerts
|

Natural coumarins from Murraya paniculata as mixed-type inhibitors of cholinesterases: In vitro and in silico investigations

Abstract: Currently, acetylcholinesterase (AChE) inhibiting drugs in clinical use, such as tacrine, donepezil, rivastigmine, and galanthamine, are associated with serious side effects and short half-lives. In recent years, numerous phytochemicals have been identified as inhibitors of cholinesterases with potential applications in the management of Alzheimer’s disease (AD). In this study three natural coumarins, 2′-O-ethylmurrangatin (1), murranganone (2), and paniculatin (3) isolated previously by our group from the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, they can be considered potential candidates for AD treatment. These coumarins show non-selective, moderate-to-good in vitro activity against both AChE and BChE via a mixed-type inhibitory mechanism ( Khalid et al, 2023 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Therefore, they can be considered potential candidates for AD treatment. These coumarins show non-selective, moderate-to-good in vitro activity against both AChE and BChE via a mixed-type inhibitory mechanism ( Khalid et al, 2023 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Structure of coumarin 2'O-ethyl murrangtin and paniculatin (135-136). [44] various position is facilitated by ketone and hydroxyl functionalities of amino acid at various locations considerably aids in the binding of the inhibitor to the receptors. Moreover, the stability of most active molecule is comparable to that of standard drug tacrine.…”
Section: Coumarinsmentioning
confidence: 99%
“…Khalid et al [44] reported that naturally derived coumarine 2’O‐ethyl murrangtin and and paniculatin (Figure 26) from the leaves of Murraya paniculata and evaluated in vitro assays against AChE and BChE. Enzyme inhibition results revealed that compound 135 and 136 was shown to be efficient inhibitors of AChE and BChE.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Systematic research found 1300 secondary metabolite chemotypes in plants, microbes, and fungi. 50 The roots of Ferulago campestris, 51 Murraya paniculata 52 leaves, Aegle marmelos 53 fruits, and tonka bean seeds contain derivatives of coumarins with several biological functions. Synthetic coumarin-based heterocyclic analogues such azoles, sulfonyl, furan, and pyrazole have promise anticancer, antitumor, and anti-proliferative properties.…”
Section: Introductionmentioning
confidence: 99%